Peramalan Kebutuhan Batubara Menggunakan Metode Single Exponential Smoothing di PT. Solusi Bangun Andalas - Gaustama Putra; Ari Rasyid Maulud (Jurnal Optimalisasi, 2020)
PT. Solusi Bangun Andalas (SBA) is one of the cement producers in Indonesia with a current production capacity of 1.6 million tons per year. Coal is the main raw material used to produce electrical energy and the combustion process at PT. Andalas Build Solutions which were imported through several suppliers. The problem that occurs is the fluctuation in the use of raw materials that is not regular becomes an obstacle in the planning of fuel procurement for the company. Errors in planning the procurement of raw materials can result in excess or shortage of inventory. Excess raw materials cause several problems, such as the company has to provide more storage space and incur additional costs for storage and maintenance so that the quality of raw materials is maintained. The problem of raw material needs can be overcome by forecasting fuel consumption needs for the following month using the Single Exponential Smoothing method. From calculations using the Single Exponential Smoothing method with α = 0.1 for kiln units, the Mean Absolute Deviation is 2286.21, the Mean Squared Error is 7,850,751.46, and the Mean Absolute Percentage Error is 26.88%. For power plant units α = 0.5 Mean Absolute Deviation is 2367.05, Mean Squared Error is 9,001,707,06, and Mean Absolute Percentage Error is 18.35%. Meanwhile, the raw material needs in the next period are 10,057.49 tons for Kiln units and 14,265 tons for power plant units.